Desenvolvimento de filmes dosimétricos fotoluminescentes à base do PBAT e do MEH-PPV para aplicação em dosimetria de altas doses de radiação gama - Thiago Schimitberger (2015)
This work presents the findings of the radioinduced photoluminescence (PL) of the biodegradable polymer poly(butylene adipate-co-terephthalate) (PBAT). In this process, a PBAT film that originally shows no photoluminescence was exposed to high doses of gamma radiation. After the irradiation process, the PBAT film becomes luminescent when excited by a LED light source with wavelength ranging from 380 nm to 420 nm. The fabrication, characterization and performance analyses of PBAT films produced and exposed to different gamma radiation doses (0 4000 kGy) show that the relationship between the photoluminescent intensity and the delivered dose PL x Dose is highly linear, allowing the development of a new dosimeter based on the different photoluminescent emission intensities of this polymer. A detailed study was carried out to analyze the relation between concentration and film thickness with the intensity of photoluminescent spectra for increasing doses. Both parameters provided a considerable increase in the photoluminescent intensity, the best relation PL x Dose being obtained for concentrations of 0.3 gml-1 and thickness of 100 micrometers (7 layers). These parameters increased the PL x dose ratio by approximately 800%, when excited with a violet LED (405 nm), in reference to the films produced in the first batch. As observed for the PL intensities, the intensities of the peak centered at 345 nm in the absorbance spectra (ABS - UV-Vis) showed a high linear relationship for high gamma doses ranging from 0 and 750 kGy. On the other hand, in the FTIR spectra, a linear relationship between the intensity of the peak centered at 3250 cm-1 and the delivered gamma doses was observed for doses between 0 and 4000 kGy. The study of the radio-degradation of gamma irradiated PBAT films, in the dose range where there is chain crosslinking formation (gel) and also chain scission, have demonstrated that both phenomena contribute to the photoluminescence. There is a relationship between the crosslinking degree and the PL curve shape. The FTIR data in this study also revealed the appearance of vibration modes belonging to the NH2 molecules, suggesting that the radio-induced photoluminescence of PBAT is due to the formation of a kind of aromatic amine: hydrocarbon ring attached toNH2 molecule. Due to the developed photoluminescent characteristics of PBAT, a second dosimeter system was studied (2D) based on the change of color emission of the polymeric blends made of PBAT and the conjugated polymer Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV). In this dosimetric system, the high doses of gamma radiation and/or the own photoemission of the PBAT matrix induces the photo-degradation of MEH-PPV polymer, synchronously decreasing its PL emission intensity with the increase of the PL intensity to PBAT, for doses ranging from 0 to 500 kGy. This mechanism implies in the color-changing emissions going from red to green. The results indicate the PBAT and MEH-PV as possible dosimetric system for use in sterile packaging of products as well as control irradiation processes, showing an innovative proposal on the use of films based on polymeric materials for practical 2D dosimetry.